2011
DOI: 10.1097/tp.0b013e31820e014e
|View full text |Cite
|
Sign up to set email alerts
|

MELD Score Less Than 15 Predicts Prolonged Survival After Transjugular Intrahepatic Portosystemic Shunt for Refractory Ascites After Liver Transplantation

Abstract: TIPS after LT can be clinically effective in patients with RA with a MELD score less than 15. This suggests that TIPS could be used as a means to extend posttransplant survival but should be carefully individualized in patients with a MELD score more than or equal to 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…85 These guidelines have also been found to be useful for placement of TIPS amongst posttransplant patients and it is recommended that TIPS be carried out only if the MELD score is <15 in these patients. 86 …”
Section: Transjugular Intrahepatic Portosystemic Placementmentioning
confidence: 99%
“…85 These guidelines have also been found to be useful for placement of TIPS amongst posttransplant patients and it is recommended that TIPS be carried out only if the MELD score is <15 in these patients. 86 …”
Section: Transjugular Intrahepatic Portosystemic Placementmentioning
confidence: 99%
“…Only few studies evaluated the clinical response to TIPS after LT in relationship to the combination of MELD score and the indication to TIPS [200,201,204,209]. Most Authors agree that transplant free survival is poorer and MELD threshold predicting poor survival is lower than those of patients with native livers [201,209,210]. The availability of the new DAAs is expected to modify the outcome of post-LT TIPS in HCV positive recipients.…”
Section: Haemophiliamentioning
confidence: 99%
“…Votes in Favour: 95%. Comment: TIPS has been shown to be effective in managing complications of portal hypertension also in patients listed for LT [25,196,197,201]. However, TIPS placement in patients on the waiting list for LT may influence several clinical aspects not only related to the outcome of primary complication of liver disease (i.e.…”
Section: Session 5: Tips In Liver Transplant Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We published the outcomes for 26 patients who underwent transjugular intrahepatic portosystemic shunt (TIPS) placement for intractable ascites after liver transplantation. 2 We also found that a Model for End-Stage Liver Disease score less than 15 predicted prolonged survival after TIPS placement in liver transplant recipients. Our experience remains the largest documented experience in the English literature.…”
mentioning
confidence: 74%